The Contested Identities of Ulster Protestants
XXI, 209 p.
Keywords: This study explores the idea voiced by journalist Henry McDonald that the Protestant, Unionist and Loyalist tribes of Ulster are '…the least fashionable community in Western Europe'. A cast of contributors including prominent politicians, academics, journalists and artists explore the reasons informing public perceptions attached to this community.